Ten things we've learned from Blockly - Fraser, Neil (2015 IEEE Blocks and Beyond Workshop (Blocks and Beyond), 2015)
Over the last four years the Blockly team has learned many lessons which are applicable to block-based programming in general. The following are a collection of ten mistakes we have made, or mistakes commonly made by others. Each issue is presented as noncontroversial folk knowledge without supporting data.